Effect of central dialysis fluid delivery system on markers of inflammation in hemodialysis patients - Yanhong Ni; Wenhui Wu; Hua Zhou; Min Li; Xiying Zhu; Hongyan Niu; Jinfeng Liu; Lina Xue; Yeqian Liu; Min Yang (BMC Nephrology, 2024)
Abstract Background The utilization of ultrapure dialysate has been shown to decrease dialysate contamination and mitigate inflammatory responses. The central dialysate delivery system (CDDS) has the potential to attain a level of purity similar to ultrapure dialysate. Nevertheless, there is limited research examining the impact of CDDS on inflammation in comparison to single-patient dialysis fluid delivery system(SPDDS). This study aims to investigate the effects of CDDS utilizing ultrapure dialysate on ameliorating the microinflammatory state in hemodialysis patients. Method A retrospective cohort clinical study enrolled a total of 125 hemodialysis patients, with 58 patients from the CDDS unit and 67 patients from the SPDDS unit. Each participant was monitored for a period of 6 months, and the repeated measurement data was analyzed using a generalized linear mixed models (GLMM). Results The average age of the studty cohort was 56.22 ± 12.64 years. The GLMM analysis showed a significant time*group interaction effect on hs-CRP changes over the follow-up period (β = -1.966, FTime* CDDS group = 13.389, P < 0.001). A linear mixed model analysis with random slope showed that a different slope was observed between CDDS group and SPDDS group (βCDDS =—0.793; βSPDDS = 0.791), indicating a decreased hs-CRP levels in CDDS group, while increased in the SPDDS group over the follow-up period. However, no significant time*group interaction effect were observed on albumin and β2-microglobulin levels during follow-up period(β2-microglobulin: β = -0.658, FTime* CDDS group = 1.228, P = 0.269; albumin: β = 0.012, FTime* CDDS group = 1.429, P = 0.233). Conclusion Using ultrapure dialysate in the CDDS is associated with an improvement in hs-CRP levels compared to standard dialysate, which might confer long-term clinical advantages.